PERBAIKAN KONSTRUKSI BUBU ELVER SKALA LABORATORIUM (Correction of Elver Trap Contruction in Laboratory Scale) - Misbah Sururi; Gondo Puspito; Roza Yusfiandayani (Marine Fisheries: Jurnal Teknologi dan Manajemen Perikanan Laut, 2016)
ABSTRACT PVC trap is used by fisherman in Java Island, southern waters to capture elver, or juvenile eels measuring < 10 gr. The problems are that trap catches too less and elver in injured condition, while buyers need a lot of good elvers for cultivating. This study tried to fix a trap construction so that function more effective and doesn’t hurt elver. All experiments were conducted in the Fishing Gear Laboratory, Bogor Agricultural University. Three sections of traps were examined were the rear cover of trap construction, entrance of trap construction and application two doors of traps. Furthermore, new traps made by three criteria were obtained. The entire test was conducted in the experimental tank containing between 30-100 elvers. The test was done as much as 20-25 times with 20 minutes soaking time. The results showed that more elvers enter the trap which does not seal, the entrance was made from nets and had two doors of the trap. The construction trap based on three criteria was more effective which could trap 355 elvers or 6.12 times more than the fisherman’s trap (58 elvers).